Synthesis and Characterization of Dual Properties Coagulant from Natural Precursors for Raw Water Treatment - Mohd Asharuddin, Syazwani; Othman, Norzila; Mohd Zin, Nur Shaylinda; Md. Din, Mohd Fadhil; Kumar, Vicky (International Journal of Integrated Engineering, 2020)
A novel coagulant with dual properties was produced by manipulating the chemical characteristics of natural precursors. In the present study, cassava peel starch (CPS) was isolated from agriculture waste and lemongrass extract was procured using soxhlet extraction using ethanol. A preliminary study consisting of chemical analysis and antimicrobial test was done onto the lemongrass extract to ensure the presence of the active group responsible for antimicrobial effect. The modified cassava peel starch (MCPS) was synthesized using novel acid-alkali grafting method to incorporate active compounds from lemongrass extract onto the starch backbone. The modified starch was subjected to Scanning Electron Microscopy coupled with Electron Dispersive X-Ray Spectrometry (SEM-EDX) for surface morphological and elementral distribution analysis. The molecular composition analysis was accomplished using Fourier Transform Infrared Spectrophotometry (FTIR) while the efficacy of the modification process was further analyze using proton Nuclear Magnetic Resonance Spectroscopy (1H NMR). The SEM-EDX and FTIR results revealed impressive changes in the physical surface morphology, elemental distribution and chemical structure of the starch post-modification. The results also indicated successful integration of lemongrass active groups onto the starch molecules which provides promising potential of the modified starch towards proposed application for water clarification and disinfection.